EDUKASI PENGENALAN UANG PALSU DAN CARA MEMBEDAKANNYA DENGAN UANG ASLI - Hidayanto, Fajar (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Counterfeit money is an imitation currency that is manufactured without legal approval of government. The manufacture, usage, and distribution of counterfeit money is very dangerous for a country economy. Either in the scale of market that have direct contact with society or in a large scale such as inflation. To prevent those, socialization should be done to each elements of society, including villager. Village that face many obstacles in accessing information will easily become the target of counterfeit money circulation. Therefore, an education about intoduction of counterfeit money and how to distinguish it with real money was proclaimed in a community service activity at Dukuh Jati, Kulonprogo, Daerah Istimewa Yogyakarta. Results of that education is people at Dukuh Jati is be more understanding about counterfeit money and can recognise it. Its circulation is expected to decline continuously.